Creating conditions for creativity in the XXI century - Ribeiro, Luísa; Magalhães, José; Laneiro, Tito (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
Creativity rises from the interaction between the acting individual, the domain he performs in, and the social environment he lives and moves in. It can be the fuel for organizational survival and/ or growth, and for workers’ development and performance. It is therefore important to understand the conditions workers can be offered in order to function creatively. Based on an interview script about creativity, 8 in-depth interviews were conducted, having an average duration of 2.5 hours each. The participants were publicly recognized creative workers, from diverse areas -Physics, Biology, Dance, Industrial Design and Visual Arts. The collected content was submitted to Alceste, a lexical analysis program. The results were the base for constructing a 99 items scale which was applied to a sample of 304 workers. After conducting a Principal Analysis Components procedure in SPSS, four factors were identified. The validity and reliability studies allowed the scale to be reduced to 26 items, and it was then validated with 236 workers. The presented instrument shows good psychometric properties and is particularly adapted to being applied in organizational ground.